PENGARUH MAHKOTA DEWA (PHALERIA MACROCARPA) TERHADAP GLUKOSA DARAH MENCIT DIABETIK : LITERATUR REVIEW - Rizka, Rizka; Khotimah, Khotimah (Universitas Pesantren Tinggi Darul Ulum, 2020)
Abstract Hyperglycemia that occurs in people with Diabetes Mellitus (DM) can have an impact on damage to small blood vessels, if in the long term it will cause neuropathy and disturbances in important organs in the body. Efforts that can be made to lower blood sugar levels in Diabetes Mellitus are by utilizing the crown of gods herbal plants, the alkaloid content in the crown of gods can reduce blood glucose by inhibiting glucose absorption in the intestine, increasing glucose transport in the blood, stimulating glycogen synthesis and inhibiting glucose synthesis. and increase glucose oxidation. The purpose of this study was to determine the effect of giving the crown of gods (Phaleria macrocarpa) on the blood glucose of diabetic mice. The research method was carried out by literature review by searching published journals online through the PubMed, ProQuest, Scholar and Sinta databases that met the inclusion and exclusion criteria. The results of the review of eleven reputable journals showed that the extract of the Dewa's Crown had a positive effect on reducing blood glucose levels. In the extract of the god's crown on the skin and flesh of the fruit, it contains saponins, flavonoids, alloxan compounds, and mineral or other compounds that can reduce glucose levels in the blood. Saponins and alloxans can reduce blood glucose levels by stimulating pancreatic ß cells so that insulin secretion increases and glucose decreases, and flavonoids are protective against damage to ß cells as insulin producers and can increase insulin sensitivity. Flavonoids are also helpful in regenerating islet cells of Langerhans. KeyWord : Phaleria Macrocarpa, Hiperglicemi, Diabetes Mellitus